Drivers of Clostridioides difficile hypervirulent ribotype 027 spore germination, vegetative cell growth and toxin production in vitro. (July 2020) - Yuille, S.; Mackay, W.G.; Morrison, D.J.; Tedford, M.C.
Abstract: Objectives: Clostridioides difficile infection (CDI) is a considerable healthcare and economic burden worldwide. Faecal microbial transplant remains the most effective treatment for CDI, but is not at the present time the recommended standard of care. We hereby investigate which factors derived from a healthy gut microbiome might constitute the colonization resistance barrier (CRB) in the gut, inhibiting CDI. Methods: CRB drivers pH, short chain fatty acid (SCFA), and oxidation–reduction potential (ORP) were investigated in vitro using C. difficile NAP1/BI/027. Readouts for inhibitory mechanisms included germination, growth, toxin production and virulence gene expression. pH ranges (3–7.6), SCFA concentrations (25–200 mM) and ORP (–300 to 200 mV) were manipulated in brain heart infusion broth cultures under anaerobic conditions to assess the inhibitory action of these mechanisms. Results: A pH < 5.3 completely inhibited C. difficile growth to optical density (OD) 0.019 vs. 1.19 for control pH 7.5. Toxin production was reduced to 25 units vs. 3125 units for pH 7.6 (1 in 5 dilutions). Virulence gene expression reduced by 150-fold compared with pH 7.6 (p < 0.05). Germination and proliferation of spores below pH 6.13 yielded an average OD of 0.006 vs. 0.99 for control. SCFA were potent regulators of toxin production at 25 mM and above (p < 0.05). Acetate significantly inhibited toxin production to 25 units independent of OD (0.8733) vs. control (OD 0.6 and toxin titre 3125) (p < 0.05). ORP did not impact C. difficile growth. Conclusions: This study highlights the critical role that pH has in the CRB, regulating CDI in vitro and that SCFA can regulate C. difficile function independent of pH.